An Aproximation to Solution of Space and Time Fractional Telegraph Equations by the Variational Iteration Method - He, Ji-Huan (Mathematical Problems in Engineering, 2012)
Sevimlican suggested an effective algorithm for space and time fractional telegraph equations by the variational iteration method. This paper shows that algorithm can be updated by either variational iteration algorithm-II or the fractional variational iteration method.